Quantity versus quality: how does level of predation threat affect Cape ground squirrel vigilance? - Unck, C.; Waterman, J.; Verburgt, L.; Bateman, Bill (Elsevier Ltd., 2009)
How individuals balance time spent satisfying nutritional needs and time spent being vigilant to protect against potential predation has received abundant attention from researchers. Evidence indicates that both social conditions and predator risk affect how individuals perceive environmental threat, however, the relative influence of each type of risk remains unclear. The risk allocation hypothesis considers how individuals respond to predation risk over time by adapting their investment in high-quality or low-quality vigilance. Here we use the risk allocation hypothesis as a guide to examine how different risk factors influence vigilance quantity and quality in Cape ground squirrels, Xerus inauris. We tested how the social conditions of age, sex, distance to a safe refuge, distance from a nearest neighbour and predator risk affect the amount of time (quantity) individuals spend vigilant. Individuals were more vigilant in areas with more potential predators and when they were further from a safe refuge or nearest neighbour. We then tested whether these risk factors that affected vigilance quantity also affected vigilance quality by measuring exclusive vigilance (high-cost, high-quality) and shared-foraging–vigilance (low-cost, low-quality). Individuals in high-predation risk areas invested more time in high-cost vigilance behaviour than in low-cost vigilance/foraging behaviour compared with individuals in low-predation risk areas. Since squirrels invested in high-cost vigilance significantly more than in low-cost vigilance regardless of distance to a refuge or other squirrels, we suggest that combined foraging with vigilance compromises vigilance to lower its quality.